What is the role of inflammatory markers in predicting spontaneous ureteral stone passage? - Senel, Cagdas; Aykanat, Ibrahim Can; Asfuroglu, Ahmet; Keten, Tanju; Balci, Melih; Aslan, Yilmaz; Tuncel, Altug (Aktuelle Urologie, 2022)
Purpose: To investigate the role of inflammatory markers in predicting the spontaneous passage of ureteral stones.Methods: We retrospectively reviewed 279 patients with ureteral stones sized 4–10 mm that were managed conservatively. The patients were divided into two groups: Group 1 consisted of 137 patients who passed the stone spontaneously; Group 2 comprised 142 patients without spontaneous stone passage. The groups were compared using the Mann-Whitney U and chi-square tests. In addition, univariate and multivariate analyses were performed to identify the significance of the parameters.Results: The mean age of the patients was 41.2 years. The patients in Group 1 had a significantly lower mean stone size, white blood cell count and neutrophil count. In addition, stone location, presence of hydronephrosis and history of urolithiasis were significantly different between the groups. Neutrophil percentage, neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were insignificantly lower in Group 1. In a multivariate analysis, stone size, distal location and hydronephrosis status significantly predicted the spontaneous stone passage. However, inflammatory markers including white blood cell count, neutrophil count and neutrophil-to-lymphocyte ratio could not determine the likelihood of spontaneous stone passage.Conclusion: Our results suggest that inflammatory markers are no meaningful parameters for the prediction of spontaneous stone passage.
Keywords: Harnleiterstein; Entzündungsmarker; Spontane Steinpassage; Prognose